2017
DOI: 10.1021/acs.iecr.6b03443
|View full text |Cite
|
Sign up to set email alerts
|

Development of Predictive Models of the Kinetics of a Hydrogen Abstraction Reaction Combining Quantum-Mechanical Calculations and Experimental Data

Abstract: The importance of developing accurate modelling tools for the prediction of reaction kinetics is well recognised. In this work, a thorough investigation of the suitability of quantum mechanical (QM) calculations to predict the effect of temperature on the rate * To whom correspondence should be addressed provide good correlated rate-constant values and to be competitive with conventional kinetic models, i.e., the Arrhenius and the three-parameter Arrhenius models. This combination of QM-calculated and experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 131 publications
0
10
0
Order By: Relevance
“…The rate constant is calculated at 1000 K, which is used to simulate the temperature in the combustion chamber of the diesel engine. Consequently, the rate constant for these initiation steps k i ,TST is computed using conventional TST 4,6,26 in the followingwhere κ is the transmission coefficient of the corrected tunneling effect, k B is the Boltzmann constant, h is the Planck constants, R is the gas constant, and Δ G i , T 0 is the standard state Gibbs free energy of activation at temperature T and pressure P 0 = 1 atm. In this work, Δ G i , T 0 has been replaced by Δ E in the calculation process of k i ,TST .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate constant is calculated at 1000 K, which is used to simulate the temperature in the combustion chamber of the diesel engine. Consequently, the rate constant for these initiation steps k i ,TST is computed using conventional TST 4,6,26 in the followingwhere κ is the transmission coefficient of the corrected tunneling effect, k B is the Boltzmann constant, h is the Planck constants, R is the gas constant, and Δ G i , T 0 is the standard state Gibbs free energy of activation at temperature T and pressure P 0 = 1 atm. In this work, Δ G i , T 0 has been replaced by Δ E in the calculation process of k i ,TST .…”
Section: Resultsmentioning
confidence: 99%
“…In this work, Δ G i , T 0 has been replaced by Δ E in the calculation process of k i ,TST . Tunneling effects may be described quantitatively as the Wigner correction factor 26,27 where v ⧧ (cm –1 ) is the magnitude of the imaginary frequency of the TST. However, the tunneling effect has little effect at high temperature, such as 1000 K. Furthermore, the imaginary frequencies of all reactions studied here are exactly similar, and the correction of the tunneling effect has no significant effect on the observed relative reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…E a has been extensively measured for ethane, , with broad agreement that the experimental value at temperatures in the vicinity of 300 K is around 8.9 kJ mol –1 . Sophisticated transition-state theory calculations, which incorporate the other temperature-dependent factors responsible for the curvature in Arrhenius plots, have shown that the experimental rate constants can be reproduced faithfully over the full measured range (200–1250 K) based on a zero-point-energy-corrected barrier height of 6.7 kJ mol –1 . In the absence of equivalent detailed information, we make the assumption that a similar ratio between empirical, room-temperature E a and threshold energies E 0 also applies to larger alkanes.…”
Section: Discussionmentioning
confidence: 99%
“… a Based on neopentane. b Based on cyclohexane. c Based on an average of 2,3-dimethylbutane and 2,3,4-trimethylpentane. d From ref . e From ref . f As estimated here by analogy with ethane, as described in the text. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation